โครงสร้างและฐานอำนาจของสมัชชาเกษตรกรรายย่อยภาคอีสาน - ปราณี ศรีสารคาม (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
This research is a study on structure and power base of the Assembly of Small-Scale Farmers of the Northeast Region of Thailand, which is led by Mr. Nakhon Sriphiphat. The study is a documentary research and als0 direct observation which has done during the year of 1996-1998. In the study, it is assumed that the establishment of the assembly of small-scale farmers caused by the problems related to landholding of the farmers. Also their exile from the landholding located in the worsen reserved forest is another reason. The strength of the assembly is due to many elements such as the precise god of the assembly, the determined leader, the effective working methods, the refined members, and the help from non-government development organizations. The line of thought used in the study is concerning the idea of a group and an assembly, a social process, a political refinement, and power base and leaders. The result of the research found out that the settlement of the assembly caused by the lack of working land. Also the government did not seriously help them. Therefore, the member of the assembly foresaw that they could solve the problems by setting up the government. Important factors in dealing with the government are divided into two main factors--internal and external factors. The internal factors include personalities and capabilities of the leader of the assembly, the effective order of the organization, and fair distribution of benefits within the organization. The external factors consist of the cooperation between the non-government organizations and other allied groups.